Upaya Peningkatan Kompetensi Guru dalam Menyusun Silabus dan RPP Melalui Supervisi Akademik Berbasis IT Yang Berkelanjutan - Rizka Khaira (INTECOMS: Journal of Information Technology and Computer Science, 2019)
Every process must always include three main activities, namely planning, implementation and evaluation. Similarly, what happens with the teaching and learning process in schools? A teacher is required to carry out planning, implementation and evaluation of learning. The learning planning process that must be carried out by a teacher includes the following main activities: 1) Making an annual program; 2) Making syllabus; 3) Making semester programs; 4) Make a plan for implementing learning; 5) And make a repeat / evaluation program. Of the five elements mentioned above, the syllabus and lesson plan are the minimum preparation for a teacher when they want to teach. Based on the results of the first semester analysis in the 2017/2018 school year at Lubuk Sikaping 2 High School, the problem arises the low ability of teachers to make learning planning, especially the preparation of syllabus and lesson plans in accordance with the 2013 curriculum. Seeing the extent to which the principal's academic supervision can improve teacher competence in the preparation of syllabus and Learning Implementation Plans. Keywords: Teachers’ Competency, Academis Supervision, Silabus